An Empirical Study of the Debt Maturity Structure of Malaysia Firms - Mohd Ariff, Ab Rahman (2011)
This study examines the empirical determinants of corporate debt maturity structure for the data set of 788 non-financial firms in Malaysia and employs a Panel Data method of Pooled Estimated Generalized Least-Squares (EGLS) with Autoregressive (AR1) for all the regression tests. The models in this study incorporate factors representing the theories of agency cost, signaling, tax considerations and matching principle. The findings of the general test reveal that the agency cost theory provides mixed results where growth proxy is not significant but the proxy of size is significant to determine the debt maturity structure. The proxies of firm quality, financial strength and liquidity have significant effects to support the signaling theory. In addition, the proxies of tax and asset maturity have no evidence to support the tax theory and matching principle respectively. The findings of test across seven industry groups document that the results are varied, except for liquidity which has significant effects on all industries. This study also discovers that Shariah-compliance has negative and significant effects. In the robustness test, the findings produce mixed results where the proxies of signaling theory in particular present contradictory results. Lastly, this study generally finds strong evidence that the larger the firm size, the longer the maturity of debt.